Answer:
8.
Step-by-step explanation:
13).
This is an equilateral triangle.
We see that all 3 angles are equal, so all sides are equal also.
So 2x - 6 = 10
2x = 16
x = 8.
Answer:
i think ur in a higher grade then me but im good w/ equations so OoOO0p
Step-by-step explanation:
equation: y = x - 6 + x^2
(6,0) (7,1) (8,4) (9,9)
I figured this out by looking at the point (6,0). To get 0 (y), you have to subtract 6. Knowing this, I subtracted 6 from the rest of the coordinates, leaving me with numbers that are able to be squared to get y. This led me to the equation x - 6 + x^2.
Answer:
Out of the four, the only statement true about the parent and the transformed function is:
"The domain of the transformed function and the parent function are all real numbers."
Step-by-step explanation:
Parent function:
f(x) = |x|
Applying transformations:
1. Stretched by a factor of 0.3:
f(x) = 3|x|
2. Translated down 4 units:
f(x) = 3|x| - 4
Transformed function:
f(x) = 3|x| - 4
We can see that:
Range of the parent function = All real numbers greater than or equal to 0.
Range of the transformed function = All real numbers greater than or equal to -4.
Domain of the parent and the transformed function is same and equal to all real numbers.
Hence, the first three statements are wrong and the fourth one is true.
14 > 10
all the numbers that bigger than 10 can replace x
2 numbers can be represented by the variables x and y.
Set up a system of equations:
![x + y = 33](https://tex.z-dn.net/?f=x%20%2B%20y%20%3D%2033)
![x - y = 1](https://tex.z-dn.net/?f=x%20-%20y%20%3D%201)
The two numbers added together will result in a sum of 33. However, one number subtracted from another will result in a difference of 1.
In both systems of equations, there are inverses of variable y. Therefore, we can combine the systems of equations by adding them together:
![(x + x) + (y - y) = (33 + 1)](https://tex.z-dn.net/?f=%28x%20%2B%20x%29%20%2B%20%28y%20-%20y%29%20%3D%20%2833%20%2B%201%29)
![2x = 34](https://tex.z-dn.net/?f=2x%20%3D%2034)
Divide both sides by 2 to get x by itself:
![x = 17](https://tex.z-dn.net/?f=x%20%3D%2017)
One of the numbers will be 17.
Plug the value into one of the equations:
![17 - y = 1](https://tex.z-dn.net/?f=17%20-%20y%20%3D%201)
Add y to both sides:
![17 = y + 1](https://tex.z-dn.net/?f=17%20%3D%20y%20%2B%201)
Subtract both sides by 1 to get y by itself:
![y = 16](https://tex.z-dn.net/?f=y%20%3D%2016)
The two numbers that sum up to 33, with a difference of 1 between them, will be 16 and 17.